A Carnian 40Ar/39Ar age for the Paasselkä impact structure (SE Finland)—An update. (18th December 2014) - Schwarz, Winfried H.; Schmieder, Martin; Buchner, Elmar; Trieloff, Mario; Moilanen, Jarmo; Öhman, Teemu
Abstract A recrystallized band of pale feldspathic impact melt in a gneissic impact breccia from the approximately 10 km Paasselkä impact structure in southeast Finland was dated via 40Ar/39Ar step‐heating. The newly obtained plateau age of 228.7 ± 1.8 (2.2) Ma (2σ) (MSWD = 0.32; p = 0.93) is equal to the previously published pseudoplateau age of 228.7 ± 3.0 (3.4) (2σ) for the impact event. According to the current international chronostratigraphic chart and using the most recent published suggestions for the K decay constants, a Carnian (Late Triassic) age for the Paasselkä impact structure of 231.0 ± 1.8 (2.2) Ma (2σ) is calculated and considered the most precise and accurate age for this impact structure. The new plateau age for Paasselkä confirms the previous dating result but is, based on its internal statistics, much more compelling.